Quality improvement initiative reduces overcrowding on labour and delivery unit in a university hospital in Haiti - Meredith Casella Jean-Baptiste; Christophe Millien; Ornella Sainterant; Maxi Raymonville; Kalinov Jim Rozensky Dameus; Marc Julmisse; Thamar Monide Julmiste; Jeanne Ginette Fanfan (BMJ Open Quality)
Background Following the first COVID-19 peak in 2020, came the seasonal childbirth peak at Hôpital Universitaire de Mirebalais (HUM). This peak is associated with overcrowding on the labour and delivery (L&D) ward. Lack of sufficient bed-space for sick neonates in the neonatal ICU at HUM, has led to overcrowding and lengthy stays of sick newborns on L&D. These conditions contribute to the subsequent lack of bed-space for newly postpartum mothers and potentially decreases quality of care for both new mothers and neonates.Methods A Maternity Task Force was created by hospital leadership to address these urgent needs. The team’s objective was to eliminate mothers and newborns laying on the floor in L&D. The Six-Sigma/DMAIC quality improvement methodology was used as the problem was urgent, demanded rapid results and centred around the process of patient flow in the institution. Process flow chart and Ishikawa diagrams were used to identify the root causes of the issues.Results An average of 22% of postpartum women did not have a bed preintervention and 0% of postpartum women were laying on the floor post intervention. An average of 33% of newborns received paediatric care on the maternity ward pre-intervention compared with an average of 17% postintervention. The team did not achieve its objective for this second indicator, which was to have less than 10% of sick newborns on the maternity ward receiving paediatric care.Conclusion HUM hospital leadership took the vital decision to form the Maternity Task Force to make changes, which consequently led to a sustainable positive and lasting impact on the lives of new mothers and their babies at the institution. The objective of 0 postpartum mothers and newborns on the ground was achieved and fewer newborns receive intensive paediatric care on the maternity ward as a result of our interventions.